Sustainable Remediation Considerations for Treatment of 1, 4‐Dioxane in Groundwater. Issue 1 (5th December 2016) - Favara, Paul; Tunks, John; Hatton, Jim; DiGuiseppi, William
Abstract : 1, 4‐Dioxane remediation is challenging due to its physiochemical properties and low target treatment levels. As such, applications of traditional remediation technologies have proven ineffective. There are a number of promising remediation technologies that could potentially be scaled for successful application to groundwater restoration. Sustainable remediation is an important consideration in the evaluation of remediation technologies. It is critically important to consider sustainability when new technologies are being applied or new contaminants are being treated with traditional technologies. There are a number of social, economic, and environmental drivers that should be considered when implementing 1, 4‐dioxane treatment technologies. This includes evaluating sustainability externalities by considering the cradle‐to‐grave impacts of the chemicals, energy, processes, transportation, and materials used in groundwater treatment. It is not possible to rate technologies as more or less sustainable because each application is context specific. However, by including sustainability thinking into technology evaluations and implementation plans, decisions makers can be more informed and the results of remediation are likely to be more effective and beneficial. There are a number sustainable remediation frameworks, guidance documents, footprint assessment tools, life cycle assessment tools, and best management practices that can be utilized for these purposes. This paper includes an overview describing the importance of sustainability in technology selection, identifies sustainability impacts related to technologies that can be used to treat 1, 4‐dioxane, provides an approximating approach to assess sustainability impacts, and summarizes potential sustainability impacts related to promising treatment technologies. ©2016 Wiley Periodicals, Inc.